THE EFFECT OF VARIED CONCENTRATION OF GARLIC (Allium sativum) ON THE CONSUMER ACCEPTANCE TO THE SPIRULINANODDLE - Panjaitan, Rinaldi; Sari, N. Ira; Buchari, Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was aimmed to determine the effect of garlic addition at different concentration on the consumer acceptance to the wet Spirulina noddle. The method used was experimental using a completely randomized design that consisting of 4 level concentration of garlic added in the noddle, namely: M0 (0%), M1(3%), M2(6%) and M3 (9%). The results showed that the highest consumer acceptance to the noddle was addition of garlic 6% (M2) in the noddle produced that was the most preferred by 93,75%. The wet Spirulina noddle produced showed the appearance good with dark green color, tasted a little bit of garlic, chewy textureand the garlicflavor was quite strong. Its proximate composition was the of content moisture 61,37%, protein 6,82%, fat 2,71%, ash 1,11% and carbohydrate 27,88% content. It was also detected the total of microbe 4,3 103cell/ g.keywords: wet noddle of Spirulina,garlic, Consumer acceptance